In situ Forming Dental Cement Loaded with Metronidazole and Doxycycline to Treat Periodontitis - Kumar, Anuj; Verma, Anurag (International Journal of Pharmaceutical Investigation, 2025)
Background In situ forming dental cements offer a novel approach to treating periodontitis by enabling localized delivery of therapeutic agents directly to the periodontal cavity. Hydroxyapatite-based materials hold promise, particularly when combined with antimicrobial agents such as metronidazole and doxycycline. This study aimed to develop and comprehensively characterize hydroxyapatite-based in situ forming dental filling materials to address the clinical needs of periodontitis treatment. Materials and Methods Dental cement formulations were prepared by combining hydroxyapatite, chitosan, carbopol 934, Glass Ionomer Cement (GIC), and GIC liquid to produce a thick paste suitable for periodontal cavity filling. Both blank and drug-loaded formulations were developed, with cementation times ranging from 60 sec (blank) to 80 sec (drug-loaded). Hardness strength testing was performed to determine structural integrity. Preformulation studies, including FTIR and DSC, confirmed the absence of material interactions. Surface roughness and bioerosion were analyzed using SEM and TEM. Biocompatibility was evaluated using MTT and Trypan blue assays with KB cell line cultures, while mucoadhesion tests were conducted on goat buccal mucosa. Antimicrobial efficacy was assessed through MIC assays against oral pathogens, and drug release profiles were measured in artificial saliva. Results FTIR and DSC analyses showed no significant material interactions in the formulations. SEM and TEM studies revealed appropriate surface characteristics and bioerosion behavior of the dental cement. Cytotoxicity assays demonstrated over 90% cell viability, indicating good biocompatibility. Mucoadhesion tests revealed excellent adhesion to goat buccal mucosa. The MIC values for Staphylococcus aureus, Escherichia coli, and Streptococcus mutans were below 10 µg/mL, confirming strong antimicrobial activity. Drug release studies in artificial saliva showed effective retention of therapeutic agents, and hardness strength tests confirmed adequate structural integrity of the formulations. Conclusion The developed hydroxyapatite-based drug-loaded dental cement demonstrated promising potential as a therapeutic agent for periodontitis treatment. These formulations combine strong antimicrobial efficacy, biocompatibility, good mucoadhesion, and suitable handling properties, making them viable for localized periodontal therapy.
Keywords: In situ forming dental cement; Periodontitis treatment; Hydroxyapatite; Metronidazole; Doxycycline; Antimicrobial efficacy; Biocompatibility; Mechanical strength